Distantly related bacteria share a rigid proteome allocation strategy with flexible enzyme kinetics - Manlu Zhu; Matteo Mori; Terence Hwa; Xiongfeng Dai (Proceedings of the National Academy of Sciences, 2025)
Bacteria are known to allocate their proteomes according to how fast they grow, and the allocation strategies employed strongly affect bacterial adaptation to different environments. Much of what is currently known about proteome allocation is based on extensive studies of the model organism Escherichia coli . It is not clear how much of E. coli ’s proteome allocation strategy is applicable to other species, particularly since different species can grow at vastly different rates even in the same growth condition. In this study, we investigate differences in nutrient-dependent proteome allocation programs adopted by several distantly related bacterial species, including Vibrio natriegens , one of the fastest-growing bacteria known. Extensive quantitative proteome characterization across conditions reveals an invariant allocation program in response to changing nutrients despite systemic, species-specific differences in enzyme kinetics. This invariant program is not organized according to the growth rate but is based on a common internal metric of nutrient quality after scaling away species-specific differences in enzyme kinetics, with the faster species behaving as if it is growing under a higher temperature. The flexibility of enzyme kinetics and the rigidity of proteome allocation programs across species defy common notions of evolvability and resource optimization. Our results suggest the existence of a blueprint of proteome allocation shared by diverse bacterial species, with implications on common underlying regulatory strategies. Further knowledge on the existence and organization of such phylogeny-transcending relations also promises to simplify the bottom–up description and understanding of bacterial behaviors in ecological communities.